Synopsis of the genus Volxemia Lameere, 1884 (Coleoptera, Cerambycidae) - Monné, Miguel A.; Monné, Marcela L. (Zootaxa, 2018)
A synopsis of Volxemia is provided. A new species Volxemia solangeae sp. nov. from the state of São Paulo, Brazil is described and illustrated. A key for the known species is provided.